Effect of sintering temperatures on structural, magnetic and microwave properties of barium ferrites/epoxy composites - Rosdi, Nurshahiera; Azis, Raba′ah Syahidah; Ismail, Ismayadi; Mustaffa, Muhammad Syazwan; Mokhtar, Nurhidayaty (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This research highlights the structural magnetic and microwave properties of nanoparticles of M-type hexagonal barium ferrites (BaFe12O19). The samples were sintered at varied sintering temperatures (800, 900, and 1000 °C). The effect of temperatures on the structural, magnetic and microwave properties was highlighted. Barium ferrites are well-known materials used for radar absorbing materials (RAM). RAM materials with good absorbing performance should have high permeability, small permittivity and high magnetic or dielectric loss at microwave frequency. High microwave absorption can be created effectively in magnetic materials, as well as wideband absorption. The structural, microstructural and microwave properties were analyzed via an X-ray Diffractometer (XRD), a Field Emission Scanning Electron Microscope (FESEM) and a Vector Network Analyzer (VNA), respectively. The XRD results showed a full phase hexagonal structure was formed in the samples sintered at 900 and 1000 ºC. BaFe12O19 composite with a thickness of 3 mm showed a minimum Reflection Loss (RL) at −9.01 dB at a frequency of 9.16 GHz at temperature 1000 ºC.